WUS-RELATED HOMEOBOX 14 boosts de novo plant shoot regeneration - Wang, Jing; Tan, Mingfang; Wang, Xuening; Jia, Lingyu; Wang, Mengping; Huang, Aixia; You, Lei; Li, Chen; Zhang, Yonghong; Zhao, Yu; Wang, Guodong (Plant physiology (Bethesda), 2023)
WUS-RELATED HOMEOBOX 14 and its putative rice ortholog boost de novo plant shoot regeneration